Moving P2P Live Streaming to Mobile and Ubiquitous Environment - Liao, Xiaofei; Jin, Hai; Jiang, Wenbin (Computing and Informatics, 2012)
Media streams distribution over a wired network to static hosts can be realized by Client/Server mode or Peer-to-Peer overlay networks. However, if the end hosts are mobile over heterogeneous wireless access networks, one needs to consider many operational issues such as network detection, handoff, join and leave latency, and desired level of quality of service, as well as caching. In the latest researches, one popular P2P live streaming system, called AnySee, over the wired network, has been deployed and widely used. Based on the AnySee system, this paper proposed and implemented one hybrid live streaming system, AnySee-Mobile, under wired and wireless environment. In the system, one wireless peer will be selected to act as an agent. One agent has two main functions, to request media from P2P overlay network as a normal peer, and to multicast media to WLAN as a multicast source. In this paper we study, how to elect one multicast agent in WLAN. Several experimentations have been made and proved that the system has good user experiences and performances.